Public service broadcasting in Serbia – challenges and perspectives from the professionals’ point of view - Krminac, Ljubica (Sociološki pregled, 2022)
This paper presents the results of a part of research into the manner in which the employees of the Serbian Broadcasting Corporation (hereinafter: the SBC) see and understand their social roles, functionality and idiosyncrasies of this media company, as public service broadcasting (hereinafter: PSB). This paper is focused on operational-level editors at the SBC and their perception of the functions and principles of PSB, as well as the implementation of such roles and principles through various forms of programming content. Empirical research, conducted by means of the focus group method, has shown that editors play a significant role in creating content and that they are fully aware of the roles of PSB. However, they are not entirely familiar with its principles. The research has demonstrated a significant discrepancy between the official editorial policies of the SBC and the views of respondents-editors regarding editorial policies of PSB.
Keywords: public service broadcasting; Serbian Broadcasting Corporation; functions; principles; focus group research